2021
DOI: 10.5946/ce.2020.245-iden
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Colorectal Cancer and Its Public Health Burden in Thailand

Abstract: Colorectal cancer (CRC) accounts for approximately 10.3% of new cancer cases in Thailand and is currently the 3rd most prevalent cancer found among the Thai population. Starting in 2017, the Thai government announced the national CRC screening program as a response to this important issue. Among the 70 million people currently residing in Thailand, 14 million require screening, while there are approximately a total of 1,000 endoscopists available to perform colonoscopy. Due to the limited resources and shortag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…Yet, because screening of CRC in young adults is not routine, the number may be an underestimation of the true regional prevalence. 22,23 Our findings align with previous studies in Asia, showing that the rise in early-onset CRC incidence is not exclusive to Western countries. 24,25 The observed increase in early-onset CRC in the Asia-Pacific region may be attributed to various factors, including heightened exposure to CRC carcinogens at a younger age.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Yet, because screening of CRC in young adults is not routine, the number may be an underestimation of the true regional prevalence. 22,23 Our findings align with previous studies in Asia, showing that the rise in early-onset CRC incidence is not exclusive to Western countries. 24,25 The observed increase in early-onset CRC in the Asia-Pacific region may be attributed to various factors, including heightened exposure to CRC carcinogens at a younger age.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the study are concerning, showing the rising incidence rates of early‐onset CRC in both the Western Pacific and SEA regions. Yet, because screening of CRC in young adults is not routine, the number may be an underestimation of the true regional prevalence 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…VHVs and local health personnel have contributed to the primary healthcare screening and control for several diseases, for example, tuberculosis, dengue infection, parasitic diseases, cancer screening and prevention, elderly care, and obesity management. 22 - 28 Even recently, their contribution was clearly shown in the fight against COVID-19. 29 Nevertheless, reports of improved control of CKD, DM, and HT by VHVs-central care were limited.…”
Section: Discussionmentioning
confidence: 99%
“…The cost-effectiveness and budget impact analyses revealed that colonoscopy was more cost-effective in a low-and middle-income country, with an Incremental Cost-Effectiveness Ratio (ICER) of United States Dollars (USD) 646.5/Quality-Adjusted Life Year (QALY) gained (28). However, providing a nationwide screening colonoscopy can be a challenge in Thailand due to low numbers of endoscopists, less than 1,000 for an estimated number of cases requiring CRC screening of 14 million (29). Hence, a population-based one-step screening colonoscopy program is less likely to succeed in resource-limited countries with a shortage of endoscopists.…”
Section: Discussionmentioning
confidence: 99%